2011
DOI: 10.1167/iovs.11-7586
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Clinical Protocol for Assessing Rod, Cone, and Melanopsin Contributions to the Human Pupil Response

Abstract: PURPOSE. To better understand the relative contributions of rod, cone, and melanopsin to the human pupillary light reflex (PLR) and to determine the optimal conditions for assessing the health of the rod, cone, and melanopsin pathways with a relatively brief clinical protocol. METHODS. PLR was measured with an eye tracker, and stimuli were controlled with a Ganzfeld system. In experiment 1, 2.5 log cd/m(2) red (640 ± 10 nm) and blue (467 ± 17 nm) stimuli of various durations were presented after dark adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
384
4
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(427 citation statements)
references
References 31 publications
22
384
4
17
Order By: Relevance
“…Melanopsins are related to circadian rhythms (Altimus et al, 2010;Berson, Dunn, & Takao, 2002;Hattar et al, 2002;Ruby et al, 2002) and the pupillary light reflex (Gooley, Lu, Chou, Scammell, & Saper, 2001;Güler et al, 2008;Park, Moura, Raza, Rhee, Kardon, & Hood, 2011;Xue et al, 2011), among other functions.…”
Section: Color Visionmentioning
confidence: 99%
“…Melanopsins are related to circadian rhythms (Altimus et al, 2010;Berson, Dunn, & Takao, 2002;Hattar et al, 2002;Ruby et al, 2002) and the pupillary light reflex (Gooley, Lu, Chou, Scammell, & Saper, 2001;Güler et al, 2008;Park, Moura, Raza, Rhee, Kardon, & Hood, 2011;Xue et al, 2011), among other functions.…”
Section: Color Visionmentioning
confidence: 99%
“…Thus, the SCN, our inner master clock that controls the day-night cycle, fails to receive adequate information from ipRGCs for synchronization. Initial attempts to monitor the function of ipRGCs using chromatic pupillometry showed that specific light stimuli can help distinguish between cone functions with and without ipRGC input by looking at the post-illumination pupillary light reflex (PIPLR), since ipRGCs are related to the PIPLR (Chen, Badea, & Hattar, 2011;Park et al, 2011).To evaluate whether one cause of bad sleep behavior in obviously demented elderly might be a dysfunction in ipRGCs, preclinical testing was performed at two homes for the elderly near Vienna, Austria, first to test its acceptance and feasibility with this population, and then to evaluate individual PIPLRs and optimize the screening method. A total of 31 participants aged 60-99 years (M = 84.2, SD = 8.8) were tested, consisting of 23 females (60-99 years, M = 85.0, SD = 8.4) and eight males (65-95 years, M = 81.9, SD = 9.4).…”
mentioning
confidence: 99%
“…To control for individual differences in resting pupil diameter, all data are reported as a percentage of the resting baseline pupil diameter (average pupil diameter during 5 s pre-stimulus period). The PIPR was quantified at six seconds after light stimulus offset (Park et al 2011). The PSQI questionnaire was scored and analysed using the global sleep score, sleep quality factor and sleep efficiency factor Chapter 4 has been published in the following study:…”
Section: Discussionmentioning
confidence: 99%
“…The participant was instructed to look straight ahead in the dark as if fixating a distant object and fixation was monitored with the IR camera. The consensual pupil reflex was measured in response to short wavelength light (464nm) with high melanopsin excitation Gamlin et al 2007;Kardon et al 2009;Park et al 2011) and to long wavelength light (638 nm) that biased activation to the outer retina (Park et al 2011) and provided a control. The corneal irradiance of the long and short wavelength stimuli was 15.1 log quanta.cm -2 .s -1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation